UPAYA KEPALA SEKOLAH MENINGKATKAN KOMPETENSI PROFESIONALISME GURU PENDIDIKAN BAHASA INDONESIA DI SMA - Paryadi Paryadi (UNIVERSITAS BENGKULU, 2015)
The objective this research are describe: the principal's efforts in improving the professional competence of teachers, how does the professional competence of teachers, the factors that support and hinder principals in improving the professional competence of teachers. This research use the method of documentation. Results of this study was the teacher can be professional if: discipline, create an atmosphere of learning better, conduct training or seminar, addition of teach hours. Supporting factors is teacher already certified, some are already S2. For inhibiting factors such as conservative minded.Keywords: efforts , improved , professionalism , competence, teacher